Assessment of patient's quality of life after using three different flap designs in periapical surgery - Assad, Mounzer; Salameh, Mazen (Latakia University Journal -Medical Sciences Series, 2018)
This study aimed to assess the patient's quality of life after the use of three different flap designs used in apicoectomy, and these designs are the trapezoidal flap, Oshenbein-Leubke flap and papilla base flap. The sample consisted of 30 patients attended the Department of Oral and maxillofacial surgery at the college of Dentistry at Tishreen University in Latakia with an indication for a periapical surgery on the front upper teeth in the period between 11.01.2013 until 04.04.2016.the assessment based on questionnaire includes four degrees edema, work and chewing and speech, recorded by the patient after two days and a week after the surgical procedure. The study showed a statistically significant difference in the chewing process where the degree of disability was lower in the papilla base flap. Also it showed that edema was less in this type of slides compared with the other two types. تقييم نوعية حياة المريض بعد استخدام ثلاث أشكال من الشرائح كمداخل جراحية في عملية قطع الذروة هدفت هذه الدراسة إلى تقييم نوعية حياة المريض بعد استخدام ثلاثة أشكال مختلفة من الشرائح المستخدمة في إجراء عملية قطع الذروة؛ وهذه الشرائح هي الشريحة شبه المنحرفة التقليدية ضمن الميزاب اللثوي و الشريحة تحت الحافة اللثوية ذات الحواف المدورةOshenbein-Leubke Flap وشريحة قاعدة الحليمة اللثوية. تألفت العينة من 30 مريض راجعوا قسم جراحة الفم والفكين في كلية طب الأسنان بجامعة تشرين في اللاذقية مع وجود استطباب لإجراء عملية قطع الذروة على الأسنان الأمامية العلوية, في الفترة ما بين 1/11/2013 حتى 4/4/2016 واعتمد التقييم على استبيان من أربع درجات يشمل الوذمة والعمل والمضغ والكلام ويسجله المريض بعد يومين و بعد أسبوع من إجراء العمل الجراحي. أظهرت الدراسة وجود فرق ذو دلالة إحصائية في عملية المضغ حيث كانت درجة الإعاقة أقل في شريحة قاعدة الحليمة. كما بينت أن الوذمة كانت أقل في هذا النوع من الشرائح مقارنةً مع النوعين الآخرين.